Binding Options for the Small Subunit-Like Domain of Cyanobacteria to Rubisco - Brandon A. Rohnke; Brandon A. Rohnke; Cheryl A. Kerfeld; Cheryl A. Kerfeld; Cheryl A. Kerfeld; Beronda L. Montgomery; Beronda L. Montgomery; Beronda L. Montgomery (Frontiers in Microbiology, 2020)
Two proteins found in cyanobacteria contain a C-terminal domain with homology to the small subunit of rubisco (RbcS). These small subunit-like domains (SSLDs) are important features of CcmM, a protein involved in the biogenesis of carboxysomes found in all β-cyanobacteria, and a rubisco activase homolog [activase-like protein of cyanobacteria (ALC)] found in over a third of sequenced cyanobacterial genomes. Interaction with rubisco is crucial to the function of CcmM and is believed to be important to ALC as well. In both cases, the SSLD aggregates rubisco, and this nucleation event may be important in regulating rubisco assembly and activity. Recently, two independent studies supported the conclusion that the SSLD of CcmM binds equatorially to L8S8 holoenzymes of rubisco rather than by displacing an RbcS, as its structural homology would suggest. We use sequence analysis and homology modeling to examine whether the SSLD from the ALC could bind the large subunit of rubisco either via an equatorial interaction or in an RbcS site, if available. We suggest that the SSLD from the ALC of Fremyella diplosiphon could bind either in a vacant RbcS site or equatorially. Our homology modeling takes into account N-terminal residues not represented in available cryo-electron microscopy structures that potentially contribute to the interface between the large subunit of rubisco (RbcL) and RbcS. Here, we suggest the perspective that binding site variability as a means of regulation is plausible and that the dynamic interaction between the RbcL, RbcS, and SSLDs may be important for carboxysome assembly and function.